Behaviour of Shear Stress of Plate Girders with Corrugated Webs - Tohamy, S. A.; Saddek, A. B.; Hamed, Asmaa Y. (International Journal For Research In Mechanical & Civil Engineering, 2016)
This paper presents analytical studies using Minimum Potential Energy Method to determine critical shear stress of local and global buckling of plate girder with corrugated webs. The elastic interactive shear buckling stress of corrugated steel web is calculated by all possible failure criteria (steel yielding, local and global buckling stresses). The results are compared with Finite element method (FEM) using ANSYS. It found that the proposed equations are a good agreement with the results FE.